ANALISIS EFISIENSI ANTAR KELOMPOK BANK DI INDONESIA: PENDEKATAN MALMQUIST TOTAL FACTOR PRODUCTIVITY INDEX - MUHAMMAD YUSUF INDRA PURNAMA (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2019)
This study examines the efficiency levels across banks in Indonesia, more specifically during the emerge of digital technology. This study used financial report data from 80 banks in 2015-2019. Data Envelopment Analysis with Malmquist Total Factor Productivity Index was employed to measure technical efficiency, pure technical efficiency as well as scale efficiency. The results suggest that large banks tend to be more efficient in term of technical efficiency relative to the small bank. However, small-scale banks tend to be more efficient in term of sale efficiency compare to the large-scale banks. The implication of this finding shows that business expansion is a source for increasing the efficiency score of small-scale banks. On the other hand, the advancement of technical and managerial terms is a source of increasing efficiency for large-scale banks. Keywords: Efficiency, Bank, Malmquist Total Factor Productivity Index